2022-RA-450-ESGO Benefit of adjuvant radiotherapy depends on molecular class of early-stage endometrial cancer. (20th October 2022) - Horeweg, Nanda; Nout, Remi A; Stelloo, Ellen; Lutgens, Ludy CHW; Jobsen, Jan J; Jürgenliemk-Schulz, Ina M; van der Steen-Banasik, Elsbieta M; Mens, Jan-Willem M; Slot, Annerie; Smit, Vincent THBM; Bosse, Tjalling; Creutzberg, Carien L
Abstract : Introduction/Background: The endometrial cancer (EC) molecular class is predictive for response to chemotherapy. Little is known about its' predictive value for response to radiotherapy. We investigated benefit of adjuvant vaginal brachytherapy (VBT) and external beam radiotherapy (EBRT) across the four molecular classes. Methodology: Participants of the randomized PORTEC-1 (n=714) and PORTEC-2 (n=427) trials were eligible if their EC were molecularly profiled according to the WHO 2020 classification. PORTEC-1 included intermediate risk EC and compared EBRT to no adjuvant treatment. PORTEC-2 included high-intermediate risk EC and compared VBT to EBRT. Locoregional recurrence-free survival (LRFS) was estimated and compared using Kaplan-Meier's methodology and log-rank tests. Correction for confounding by predefined clinicopathological factors was done using Cox proportional hazards models. Results: 881 patients with a median follow-up of 11.3 years were included. Patient and tumour characteristics are presented in table 1 . EC were classified as POLE -mutant ( POLE mut, 7.3%) mismatch-repair deficient (MMRd, 28.0%), p53-abnormal (p53abn, 9.1%) and non-specific molecular profile (NSMP, 55.6%). Overall, adjuvant radiotherapy significantly improved LRFS ( figure 1A ). In POLE mut EC no LR were observed ( figure 1B ). In MMRd EC, VBT and EBRT did not significantly improve LRFS ( figure 1C ). In p53abn EC, EBRT but not VBT significantly improved LRFS ( figure 1D ). In NSMP EC, both EBRT and VBT significantly improved LRFS. Adjuvant radiotherapy and molecular class retained significant impact on LRFS after correction for clinicopathological risk factors ( table 1 ). Conclusion: Benefit of adjuvant radiotherapy in early-stage endometrioid EC differs between EC molecular classes. Omitting radiotherapy seems safe in early-stage POLE mut EC. Benefit of radiotherapy in MMRd EC is uncertain as only a small, non-significant reduction in LR was observed. In p53abn EC, EBRT significantly improved LRFS, in contrast to brachytherapy and no adjuvant treatment. NSMP EC seem to have a clear benefit of radiotherapy; VBT seems sufficient for locoregional tumour control.